The Analysis Study of Effectiveness of Oral Isotretinoin for Treatment of Mucocutaneous Human Papilomavirus Infections : A Comprehensive Systematic Review - Putri, Putu Mahadevy Pradnyandhari; Pramartha, Made Krisna Wibawa (The Indonesian Journal of General Medicine, 2024)
Background: Oral isotretinoin (13-cis-retinoic acid) is a retinoid, derivedfrom vitamin A. Warts constitute the most frequently observed dermatological manifestations of human papillomavirus (HPV). The aim: The aim of this study to show about oral isotretinoin for treatment of mucocutaneous human papillomavirus infection. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: low dose oral isotretinoin when combined with topical tretinoin 0.1% can be superior to low dose oral isotretinoin alone in terms of faster resolution of lesions in addition to complete clearance with minimal side effect profile.